Economics / Michael Parkin - Parkin, Michael (Estados Unidos de America: Addison-Wesley Publishing Comapny, 1939)
What is economics?, making and usisng graphs, production, speialization, and exchange, demand and supply, elasticity, markets in action, utility and demand, possibilities, preferences, and choices, organizing production, output an dcosts, competition, monopoly, monopolistc competition and oligopoly, pricing and allocating factors of production, labor markets, capital and natural resource markets, uncertainty and information.
contents, glossary, graphics, table
Col. Admón
Keywords: 1. ECONOMICS 2. ECONOMETRY 3. ADMINISTRATION